IMPROVING PRONOUNCIATION SKILLS WITH ELSA SPEAK AN AI-BASED LEARNING - Sherly Marlinda; Nyimas Nur Huda (Jurnal Intelek Insan Cendikia, 2024)
This research focuses on the importance of English pronunciation in language teaching, particularly for students using English as a foreign language. The study highlights the significance of accurate pronunciation in language interpretation and communication, emphasizing the impact of mispronunciation on language comprehension. With the advancement of technology in the Society 4.0 era, the use of pronunciation software, such as the English Language Speech Assistant (ELSA), has become a valuable tool for improving students' pronunciation skills. The ELSA application utilizes speech recognition technology to detect and correct pronunciation errors, providing interactive feedback to enhance students' pronunciation abilities. By incorporating AI-based learning through ELSA Speak, this research aims to enhance students' pronunciation proficiency and promote effective language learning strategies.